Infrastructure as code (IAC) cookbook : over 90 practical, actionable recipes to automate, test and manage your infrastructure quickly and effectively /: over 90 practical, actionable recipes to automate, test and manage your infrastructure quickly and effectively. (2017) - Jourdan, Stephane; Pomès, Pierre
No abstract available